Comparison of Smoking Cessation Program Registration, Participation, Smoking Cessation Medication Utilization, and Abstinence Rates Between Smokers With and Without Schizophrenia, Schizo-affective Disorder, or Bipolar Disorder. Issue 5 (9th October 2021) - Kertes, Jennifer; Stein Reisner, Orit; Grunhaus, Leon; Nezry, Ronit; Alcalay, Tamar; Azuri, Joseph; Neumark, Yehuda
Abstract: Introduction: People with serious mental illness (SMI) are three times more likely to smoke and be heavy smokers than smokers without SMI. Counseling combined with smoking cessation medication (SCM) is the recommended treatment. However, until 2017, SCM prescription for SMI smokers was discouraged (FDA black box warning). This study compared use of smoking cessation programs (SCP) and SCM between smokers with and without SMI. Aims and Methods: Data regarding SCP and SCM use were extracted from the database of a large HMO that offers free Group and telephone SCP. SCP registration, participation, completion, and abstinence rates between July 2013 and December 2019 were compared between smokers with and without SMI, controlling for demographic and health variables. Results: 48 000 smokers registered for a SCP during the study period. Smokers with SMI were 1.8 times more likely to register for a SCP than smokers without SMI. Smokers without SMI were, however, 1.2 times more likely to start the SCP, 1.5 times more likely to complete the SCP, and 1.6 times more likely to have quit by the end of the program. The strongest factors predicting abstinence were SCP completion and SCM use. Smokers with SMI were less likely to purchase SCM, although their purchase rate increased after the black box warning was lifted. Conclusions: Smoking cessation programs and SCM use should be encouraged in the SMI population. Providing support during the quit attempt and adapting SCP to the needs of smokers with SMI, combined with SCM prescription promotion, should improve abstinence. Implications: Smokers with serious mental illness (SMI) were more likely to seek professional help to quit smoking than non-SMI smokers, with over 30% achieving abstinence, discrediting healthcare professional beliefs that SMI smokers don't want to and cannot quit. Smoking cessation program (SCP) completion and smoking cessation medication (SCM) utilization were the strongest predictors of abstinence. SMI smokers were more likely to drop out of SCPs and less likely to use SCMs. Providing support during the quit attempt and adapting SCPs to the needs of smokers with SMI, combined with SCM prescription promotion, should improve abstinence.